A new species of Scutiger (Anura : Megophryidae) from Nagaland, North Eastern, India - Das, Indraneil; Chanda, Shyamal Kumar (British Herpetological Society, 2000)
The anuran genus Scutiger, assigned by some (e.g. Frost, 1 985 and Duellman, 1 993) to the family Pelobatidae, and by other more recent workers (e.g. Fu et al., 1 997; Fu & Murphy, 1 997) to Megophryidae, contains 32 nominal species. While the apparent centre of radiation of the genus is China, three species (S. nyingchiensis Fei, 1 977; S. occidentalis Dubois, 1 977 and S. sikimmensis Blyth, 1 854) have been recorded from India (Inger & Dutta, 1 986; Dutta, 1 997). Until now, a single species, S. sikimmensis, has been recorded from the north-eastern region of India (see Chanda, 1 994). A well-preserved adult male Scutiger received by the Zoological Survey of India serves as the basis for the description of a new species. The material was collected from Nagaland, in north-eastern India